Dynamisms of financialization: Circuits of power in globalized production networks. (June 2018) - Pedraza-Acosta, Isabel; Mouritsen, Jan
This article analyses the dominant ideological mode of rationality of financialization, its operationalization via accounting devices and deployments in political intra- and inter-organizational processes, and its dynamisms in global production networks. It asks how are political processes informed and conditioned by calculative devices that mediate financialization processes? Drawing on a study of a French multinational corporation whose accounting devices – one concerning performance that requires suppliers to be 'poor' and another concerning risk that requires suppliers to be 'rich' – the article focuses on the dynamic of circuits of power. Accounting devices provide one-sided incentives by categorizing suppliers as costs, silencing the industrial rationality of the network where suppliers are the capabilities and skills needed by the multinational corporation. Such tensions put the network at risk, as when the suppliers went bankrupt, the multinational corporation was devoid of its industrial competencies. Financialization is ambiguous. Its devices are not inherently facilitative of systemic powers but reflect an ideological mode of rationality and political processes that produce overflows. The associated circuits of power show that systemic power is never eternal but dynamic. Circuits of power develop ambiguous political processes that push disruptive dynamisms of financialization processes in global production networks. Financialization produces costly tensions.